Sources and ages of fine-grained sediment to streams using fallout radionuclides in the Midwestern United States. (1st June 2017) - Gellis, Allen C.; Fuller, Christopher C.; Van Metre, Peter C.
Abstract: Fallout radionuclides, 7 Be and 210 Pbex, sampled in bed sediment for 99 watersheds in the Midwestern region of the United States and in 15 samples of suspended sediment from 3 of these watersheds were used to partition upland from channel sources and to estimate the age or the time since the surface-derived portion of sediment was on the land surface (0–∼1 year). Channel sources dominate: 78 of the 99 bed material sites (79%) have >50% channel-derived sediment, and 9 of the 15 suspended-sediment samples (60%) have >50% channel-derived sediment. 7 Be was detected in 82 bed sediment samples and all 15 suspended-sediment samples. The surface-derived portion of 54 of the 80 (68%) streams with detectable 7 Be and 210 Pbex were ≤ 100 days old and the surface-derived portion of all suspended-sediment samples were ≤ 100 days old, indicating that surface-derived fine-grained sediment moves rapidly though these systems. The concentrations of two hydrophobic pesticides–DDE and bifenthrin–are correlated with the proportion of surface-derived sediment, indicating a link between geomorphic processes and particle-associated contaminants in streams. Urban areas had the highest pesticide concentrations and the largest percentage of surface-derived sediment. Although the percentage of surface-derived sediment is less than channel sources at most of the study sites, the relatively young age of the surface-derived sediment might indicate that management actions to reduce sediment contamination where the land surface is an important source could have noticeable effects. Highlights: An approach to determine sources of sediment at regional scales. Channel sources of sediment dominate in Midwestern streams of the United States. The portion of sediment that is surface derived is relatively young <100 days. The concentrations of two hydrophobic pesticides –DDE and bifenthrin–are correlated with the proportion of surface-derived sediment.